(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article covers information on the growth and development of the body of Primary School students, physical rehabilitation of children, rehabilitation-oriented autoreflex special physical exercises,the formation of spiritual moral values, increased physical activity, yoga poses and control exercises, the formation of the correct figure.